COMPARATIVE EFFICACY OF SODIUM–GLUCOSE COTRANSPORTER-2 INHIBITORS VERSUS PLACEBO ON CARDIOVASCULAR MORTALITY IN ADULTS WITH HEART FAILURE: A META-ANALYSIS OF RANDOMIZED CONTROLLED TRIALS - DAS, PRANAB; PAL, MAHAPRASAD; AKRAM, WASIM; DAS, BODHISATYA (International Journal of Current Pharmaceutical Research, 2026)
Objective: To evaluate the effect of sodium–glucose cotransporter-2 (SGLT2) inhibitors compared with placebo on cardiovascular mortality in adults with heart failure using evidence derived exclusively from randomized controlled trials. Methods: A systematic review and meta-analysis of randomized controlled trials was conducted in accordance with PRISMA 2020 guidelines. Electronic databases were searched to identify eligible trials enrolling adult patients with heart failure that directly compared an SGLT2 inhibitor with placebo and reported cardiovascular mortality. Data were extracted from full-text publications, and risk ratios (RRs) with 95% confidence intervals (CIs) were pooled using an inverse-variance fixed-effect model. Statistical heterogeneity was assessed using Cochran’s Q test and the I² statistic. Results: Four large, double-blind randomized controlled trials comprising 20,725 participants met the inclusion criteria. Across individual studies, SGLT2 inhibitor therapy was consistently associated with a lower risk of cardiovascular death compared with placebo. The pooled analysis demonstrated a statistically significant reduction in cardiovascular mortality with SGLT2 inhibitors (pooled RR = 0.88; 95% CI: 0.81–0.96). Statistical heterogeneity was negligible (I² = 0%), indicating high consistency across trials. Conclusion: This meta-analysis demonstrates that SGLT2 inhibitors significantly reduce cardiovascular mortality in adults with heart failure. The consistency of benefit across heart-failure phenotypes and the low heterogeneity support the robustness of these findings and reinforce the role of SGLT2 inhibitors as a foundational component of contemporary heart-failure therapy.